Identifikasi arah rembesan lindi menggunakan metode geolistrik resistivitas konfigurasi dipole-dipole di sekitar tempat pembuangan akhir (TPA) sampah sekoto kabupaten Kediri - Yuni Iswahyu Ratih; Daeng Achmad Suaidi; Samsul Hidayat (Jurnal MIPA dan Pembelajarannya (JMIPAP), 2021)
Garbage is matter which is serious enought to society especially in the main city. Increasing number of society will affect to increasing garbage either as resulted. Volume of garbage which al ways increase without measuring last process of garbage will appear many problems for example, leachate seepage. Leachate is a liquid waste resulted of biology decomposition. Leachate soaks to bottom groundwater will affect decreasing level of field water and allergy on the skin. The aim of this research is to know leahate accumulation and direct seepage arround landfill Sekoto. The method will be conducted by field research by geoelectric configuration diple-dipole. Firstly, the writter survey the location to know the condition of research. Then collected data with 5 line arround landfill Sekoto use resistivitymeter. The data will be process using software Res2dinv and Voxler. Software Res2dinv to show the leachate seepage base on resistivity rock value. Software Voxler is used to show direct seepage as 3 dimension. The research finding shows that lye had been permeated in the south of garbage-can with the leachate seepage reaching 6.79 meters. While, in the north of garbage-can, there was no leachate seepage found. In the west road of Garbage Dump and near to leachate waste pipe, it had been found the leachate seepage reaching 11.8 meters. In summary, the direction of leachate seepage in Garbage Dump is congruence with river flow and the distribution of leachate horizontally.